2005
DOI: 10.1097/01.brs.0000186591.17114.e9
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Gene Expression and Loss of Anular Architecture Caused by Experimental Disc Degeneration–An In Vivo Animal Study

Abstract: Experimental moderate disc degeneration is characterized by a loss of BMP-2/4 and COL2 positive cells, although gene expression of disc constituents, catabolic enzymes, and growth factors is stimulated to reestablish disc integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 36 publications
5
44
0
Order By: Relevance
“…LeMaitre et al found that, unlike MMP-1 which seem to be constitutively expressed in adults, the MMP-13 gene is exclusively transcribed in aging and degenerating discs [34]. These data were confirmed by Guehring et al who have shown in an experimental rabbit model that compression-induced disc degeneration is accompanied by an up-regulation of both collagenase genes [18].…”
Section: Discussionsupporting
confidence: 76%
“…LeMaitre et al found that, unlike MMP-1 which seem to be constitutively expressed in adults, the MMP-13 gene is exclusively transcribed in aging and degenerating discs [34]. These data were confirmed by Guehring et al who have shown in an experimental rabbit model that compression-induced disc degeneration is accompanied by an up-regulation of both collagenase genes [18].…”
Section: Discussionsupporting
confidence: 76%
“…Guehring and collaborators (39) have also shown a significant up-regulation of COL1A2 in compressed discs in an animal model. However, to explain differences in gene associations between the specific disc regions, we must also consider that at different stages of degeneration, different genes may be important and that the influence of different environmental factors and other genes (e.g., vertebral anthropometrics) can vary between discs.…”
Section: Discussionmentioning
confidence: 98%
“…In degenerative disc models, the decreased expression of the BMP-2 gene may represent a failed reparative response to injury (20,21). In an external-compression degenerative disc model, immunohistochemical evaluation of the compressed discs demonstrated a loss of the annular architecture and a significant reduction in the number of BMP-2-positive cells, whereas gene expression analysis showed a significant upregulation of BMP-2 (22). In a rabbit annular stab-injury model, there was a relative decrease in BMP-2 mRNA levels, followed by a consequent increase close to the preoperative levels (20).…”
Section: Discussionmentioning
confidence: 98%